FUNCTIONS OF CODE SWITCHING IN AN ENGLISH CLASS - Semi Sukarni (Universitas Islam Negeri Walisongo Semarang, 2016)
Code Switching (CS) is shifting from one language to another in a conversation. It is a normal every day practice among people in the world for various reasons and usually an unconscious activity. This language switching might not be the whole sentence, but also can occur in brief phrases or words. Therefore, in this study, using CS as a medium of instruction was focused on. The objective of this study is to describe the functions of CS done both by teacher and students.The data for this study were collected at State Junor High School 18 of Purworejo on 12th and 13th July, 2013. The researcher chose the eighth grade VIII G class of SMP Negeri 18 Purworejo. The data were taken twice (two meetings; 2x80 minutes). There are 40 students and one English teacher, Ms. Titik Kusumawati, S.Pd. The data of the study were collected in the form of recorded class- room interaction with videocamera and the observer’s ﬁeld notes. The two types of database were examined in order to identify what kinds of activity were involved in the teacher-student interaction. The analysis of the data was adobted from Sert (2005). The func- tions of student CS includes equivalence, ﬂoor holding, reiteration, and conﬂict control. While the functions of teacher CS include- schecking understanding, asking clariﬁcation, clariﬁcation, transla- tion, and socializing adobted from Flyman-Mattson and Burenhult (1999).Code Switching (CS) is shifting from one language to another in a conversation. It is a normal every day practice among people in the world for various reasons and usually an unconscious activity. This language switching might not be the whole sentence, but also can occur in brief phrases or words. Therefore, in this study, using CS as a medium of instruction was focused on. The objective of this study is to describe the functions of CS done both by teacher and students.The data for this study were collected at State Junor High School 18 of Purworejo on 12th and 13th July, 2013. The researcher chose the eighth grade VIII G class of SMP Negeri 18 Purworejo. The data were taken twice (two meetings; 2x80 minutes). There are 40 students and one English teacher, Ms. Titik Kusumawati, S.Pd. The data of the study were collected in the form of recorded class- room interaction with videocamera and the observer’s ﬁeld notes. The two types of database were examined in order to identify what kinds of activity were involved in the teacher-student interaction. The analysis of the data was adobted from Sert (2005). The func- tions of student CS includes equivalence, ﬂoor holding, reiteration, and conﬂict control. While the functions of teacher CS include- schecking understanding, asking clariﬁcation, clariﬁcation, transla- tion, and socializing adobted from Flyman-Mattson and Burenhult (1999).